A fructan from Anemarrhena asphodeloides Bunge showing neuroprotective and immunoregulatory effects. (1st February 2020) - Zhang, Shaojie; Zhang, Qi; An, Lijun; Zhang, Jiaojiao; Li, Zhengguo; Zhang, Jie; Li, Yuhao; Tuerhong, Muhetaer; Ohizumi, Yasushi; Jin, Jin; Xu, Jing; Guo, Yuanqiang
Graphical abstract: Highlights: A novel fructan, AAP70-1, was isolated from A. asphodeloides for the first time. The structure and morphology of AAP70-1 were characterized for the first time. AAP70-1 exhibited significant neuroprotective activity in an SH-SY5Y cells injury model. AAP70-1 significant enhanced the immunoregulatory activity of RAW264.7 cells. Abstract: A novel polysaccharide, AAP70-1, was isolated from Anemarrhena asphodeloides for the first time. The primary structural analysis revealed that AAP70-1 was composed of glucose and fructose, had an absolute molecular weight of 2720 Da, and contained a (2→6)-linked β -D-fructofuranose (Fru f ) backbone and a (2→1, 6)-linked β -D-Fru f side chain with an internal α -D-glucopyranose (Glc p ) in the form of a neokestose. To explore the potential factors responsible for the medicinally relevant bioactivities of A. asphodeloides, a biological assay was performed. Using flow cytometry analysis, AAP70-1 was experimentally shown to have neuroprotective effects, and it can prevent and ameliorate neurological damage via reducing apoptosis. The immunomodulation assay further revealed that AAP70-1 can significantly improve immune function by promoting phagocytic capacity and the secretion of cytokines (IL-6, IL-1 β and TNF- α ) in RAW264.7 cells. These results suggest that AAP70-1 has potential as a therapeutic agent for central nervous system diseases or as an immunomodulatory agent.